1958
DOI: 10.1002/qj.49708435902
|View full text |Cite
|
Sign up to set email alerts
|

Some measurements on undercutting cold air

Abstract: S m YFrom time series of closely-spaced upper-wind (pilot-balloon) measurements in the rear of synoptic lines of wind shift and cooling, the configuration of the elevated wind-shear layer and the strength of the flow beneath are deduced. The height of the shear layer does not rise uniformly with time, but at one stage remains constant or decreases, before resuming a sustained rise. It is demonstrated by the method of dynamic similarity that this phenomenon is broadly the counterpart of the friction head on den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1959
1959
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…There appear to be three types of sea breeze reported in the literature. The first is the classical air-mass front as reported by Koschmieder (1935), Berson (1958), Wallington (1959Wallington ( , 1965, Simpson (1965), Frizzola and Fisher (1963), Leopold (1949), and Rao (1955), in which the sea-breeze front is characterized by a sharp temperature fall, humidity rise, and sharp wind-velocity change.…”
Section: State Of Knowledgementioning
confidence: 85%
See 3 more Smart Citations
“…There appear to be three types of sea breeze reported in the literature. The first is the classical air-mass front as reported by Koschmieder (1935), Berson (1958), Wallington (1959Wallington ( , 1965, Simpson (1965), Frizzola and Fisher (1963), Leopold (1949), and Rao (1955), in which the sea-breeze front is characterized by a sharp temperature fall, humidity rise, and sharp wind-velocity change.…”
Section: State Of Knowledgementioning
confidence: 85%
“…The depth of the sea breeze is greater in onshore flow conditions than in offshore flow conditions. For flow parallel to the coast, certain features may be inferred from Berson's (1958) work to complement the above cited papers. With an anticyclone offshore, the depth of the sea breeze is shallow and the front intense, in general, similar to the conditions for offshore gradient flow.…”
Section: State Of Knowledgementioning
confidence: 96%
See 2 more Smart Citations
“…Several measurements indicated that the leading edge of some cold fronts showed a correspondence to gravity (density) currents (Berson 1958;Clarke 1961;Hobbs and Persson 1982;Carborne 1982;Garratt and Physick 1986). A gravity current is a mass of highdensity (cold) fluid that flows along a horizontal bottom, displacing ambient lesser-density (warmer) fluid (e.g., Glickman 2000).…”
Section: Introductionmentioning
confidence: 99%